PROFIL KONDISI MENTAL ATLET SEPAK BOLA DI KLUB AS ABADI KOTA PEKANBARU - Wahyudi, Wahyudi; Vai, Aref; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: The problem in this study is based on field observations on thefootball team at As Abadi Club, Pekanbaru City, the mental / psychological condition ofthe athletes has not been as expected, so it is very influential in the achievement ofathletes' achievements in soccer games. This study aims to determine how the profile ofthe mental / psychological condition of the soccer players in As Abadi Football Club,Pekanbaru City. The sampling technique was a sample population of 15 athletes. Basedon the results carried out from the calculation of the analysis, it can be concluded thatthe mental / psychological condition profile of the athlete can be categorized as